Assessment of genotoxic effects of wastewater of Kitchener pool, Nile Delta Region, North Egypt, using Allium test - Aziza S. El-Kholy; Soliman A. Haroun; May Labeeb (Beni-Suef University Journal of Basic and Applied Sciences, 2023)
Abstract Background In the present study, Allium test bioassay was utilized to evaluate the effects of mixed wastewater of agricultural and sewage effluents at Kitchener pool, Gharbia governate, Middle Delta region, North Egypt. Germination indices, mitotic index and aberrations, α, β-esterase isozymes and inter-simple sequence repeat (ISSR) fingerprinting were tested by different concentrations of the wastewater (tap water as control, 25%, 50% and 100% wastewater). Results Water analysis recorded high levels of electrical conductivity, cations and anions compared to control, but were in the permitted limits according to FAO (Food and Agricultural Organization) except Mg2+ and K1+ were above the limits. P, N and heavy metals as Pb, Mn and Ni were also higher than the control. Germination indices showed reduction for all parameters studied (root and shoot lengths, root and shoot fresh and dry weights, and tolerance index). Mitotic index decreased, and the percentage of mitotic aberrations increased as the concentration of treatments increased and the time prolonged. Different types of aberrations were recorded in all treatments and its percentage is time and dose independent. Goat cells are the most common type recorded after different times in all treatments. The expression of α, β-esterase enzymes showed variation in different treatments compared to control and ISSR profiles showed considerable polymorphism. Concentration of 25% mixed water induced different profiles for expression of both α- and β-esterase from other treatments, and the cluster analysis based on polymorphism in ISSR fingerprinting revealed the distinction of plants treated with this concentration and the control plants from those treated with high concentrations. Conclusion It was suggested that concentration of 25% mixed water may be suitable for growth and act as fertilizer. Mixed water from this pool may be genotoxic for Allium cepa plants at early growth if it is used for irrigation in its present form and usage of this wastewater for agricultural purposes may be harmful and must be partially treated and biologically tested before use.